Risk factors associated with early childhood caries in autonomous province of Vojvodina, Republic of Serbia - Tušek, Ivan F.; Tušek, Jasmina; Ukropina, Snežana (Vojnosanitetski pregled, 2017)
Background/Aim. Early childhood caries (ECC) is still unexplored in Vojvodina an autonomous province of the Republic of Serbia. The aim of this study was to determine its prevalence in preschoolers and to define the risk factors that affect the prevalence of this disease. Methods. The survey was designed as a cross-sectional analytical study of preschool children in the region of Vojvodina, the Republic of Serbia. Sample type has been projected as a systematic sample and contained both parents and their children from 13 to 71 months of age. The study was designed with a dental examination of children and self-administered questionnaire which included: gender of children, self-referred socioeconomic status, parental education, oral status and health information level about parents and their child, child oral hygiene habits, type of feeding during infancy, consumption of sweets, and use of medical syrups. The data was further analyzed using the SPSS for Windows Microsoft Excel, version 21. The percentage of caries-free children was compared using χ2 test; one way ANOVA was used to compare the mean disease indices at the 5% level of significance. Categorical variables were compared for statistical difference across groups using contingency χ2 tests together with multinomial logistic regression modeling regarding the predictive model for ECC prevention. Results. The case group involved 452 (52.44%) males and 410 (47.56%) females. The prevalence of ECC in children 13-71 months old was 46.64%. Logistic regression model showed that those children who used sweets between meals, were more likely to have ECC (OR = 181.16; 95%, CI = 84.29–389.34), as well as those who used medical syrups more than five times a year in comparison to those who never used medicines (OR = 8.08; 95% CI = 3.78–17.27), among parents with poor oral status (OR = 3.09; 95% CI = 1.65–5.79) and low health informed parents (OR = 217.57; 95% CI = 84.46–560.50). Conclusion. This study suggests an association between the examined risk factors and high ECC prevalence in preschool children in Vojvodina.